Evaluasi Kelayakan Investasi Ekspansi Kampung Inggris Pontianak melalui Analisis Penganggaran Modal - Sy Ilham Zultami; Erwin Febriansyah; Teddy Rianto L Gaol; Grace Talenta Hutagalung (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to evaluate the financial feasibility of the planned expansion of Kampung Inggris Pontianak (KIP) into the Purnama area using a capital budgeting approach. The methods employed include the Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR) to assess the efficiency and profitability of the investment. Research data were collected through interviews with KIP management, field observations, and financial reports from previous branches (Paris 2, Ampera, and Podomoro).The analysis indicates that the total initial investment required is IDR 230,000,000, with projected annual net cash flows increasing through the third year. The results show a Payback Period of 2.5 years, a Net Present Value of IDR 715,580,000, and an Internal Rate of Return of 78.45%, all of which meet the financial feasibility criteria. Sensitivity analysis further demonstrates that the project remains financially viable even under conditions of declining profit margins or student enrollment. Therefore, the expansion project of Kampung Inggris Pontianak to the Purnama area is considered financially feasible and profitable, with the potential to contribute positively to the development of non-formal education in Pontianak.